Author Correction: Injectable tissue integrating networks from recombinant polypeptides with tunable order. Issue 12 (December 2018) - Roberts, Stefan; Harmon, Tyler; Schaal, Jeffrey; Miao, Vincent; Li, Kan; Hunt, Andrew; Wen, Yi; Oas, Terrence; Collier, Joel; Pappu, Rohit; Chilkoti, Ashutosh
In the version of this Article originally published, one of the authors' names was incorrectly given as Jeffery Schaal; it should have been Jeffrey L. Schaal. This has been corrected in all versions of the Article.